2012
DOI: 10.21273/horttech.22.2.237
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Platform for Measuring Canopy Photosynthetically Active Radiation Interception in Orchard Systems

Abstract: A mobile platform was developed for measuring midday canopy photosynthetically active radiation (PAR) interception in orchards. The results presented are for almond (Prunus dulcis) and walnut (Juglans regia), but the mobile platform can be used in other orchard crops as well. The mobile platform is adjustable to accommodate orchard row spacing from 4.8 to 7.8 m and is equipped with a global positioning satellite (GPS) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The results showed that canopy light interception or LAI of individual trees are poor predictors of almond yield. Making measurements over a wide range of canopy light interception values, Lampinen et al (2012) found that the correlation between MLB fPAR and yield of entire orchard rows was moderate for almonds (R 2 = 0.49-0.59 for two consecutive years) and high for walnuts (R 2 = 0.62 and 0.83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that canopy light interception or LAI of individual trees are poor predictors of almond yield. Making measurements over a wide range of canopy light interception values, Lampinen et al (2012) found that the correlation between MLB fPAR and yield of entire orchard rows was moderate for almonds (R 2 = 0.49-0.59 for two consecutive years) and high for walnuts (R 2 = 0.62 and 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…Lampinen et al (2012) found that canopy light interception in almonds, walnuts and other tree crops correlates well with maximum potential yield. They reported that the maximum sustainable yield in commercial almond orchards of California is 56 kernel kg ha −1 per each unit percent light intercepted by the canopy.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, the natural light in the PAR region (400-700 nm) below the canopy (PARb) was measured during the surveys using a series of AccuPAR LP-80 ceptometers (Decagon Devices, Inc., Pullman, WA, USA) connected to a datalogger (CR3000, Campbell Scientific, Logan, UT, USA) and mounted at a height of 0.4 m from the ground level on two side-arm bars of a Kawasaki Mule utility vehicle or Mobile LightBar (MLB) [48]. Measurements of light interception were taken during clear skies at solar noon ± 1 h. The MLB is normally operated at a speed of about 2.8 m s −1 , scanning the light transmitted by the canopy every 0.3 m down the orchards rows and integrating segments of 0.4 m across the rows [49].…”
Section: Par Light Interception By the Tree Canopymentioning
confidence: 99%
“…Among the variables that have been shown to impact yield in almond, canopy interception of photosynthetically active radiation (PAR), is directly related to maximum potential yield of almonds (Zarate-Valdez et al, 2015). Lampinen et al (2012), reported that the maximum sustainable yield in the most productive commercial almond orchards is 56 kernel kg/ha per unit PAR intercepted by the canopy. Percent light interception at the orchard level is determined by canopy structure, e.g., total leaf area and health at the individual tree level, as well as row and tree spacing; while the location of the orchard (latitude) and cloud fraction affect the total amount of PAR incident on the canopy.…”
Section: Introductionmentioning
confidence: 99%